Studi Kasus Peraturan Pemerintahan Republik Indonesia No.51 Tahun 2009 tentang Pekerjaan “Kefarmasian Apoteker di Jombang Diduga Langgar Kode Etik Kefarmasian”: Case Study of Government Regulation of The Republic Of Indonesia No.51 of 2009 Concerning Pharmaceutical Work “Pharmacist in Jombang Suspected of Violating Pharmaceutical Code of Ethics” - Sophy Wulandari; Rima Putri Ramadhani; Muhammad Naufal Nurhadi Hidayat (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2024)
Bacakground: Pharmacists are health workers who have important responsibilities in drug management. However, there are still many violations of the code of ethics and lack of understanding of the regulations governing pharmaceutical practices, which can potentially endanger patients. Aim: This study aims to analyze the impact, sanctions, and legal protection related to the provision of expired drugs to patients. Method: The method in this research is qualitative descriptive analysis. The author collected data from various sources, including relevant regulations, case studies, and academic literature, to assess pharmacists' compliance with applicable pharmaceutical regulations. Results: Many pharmacists have not fully complied with existing regulations, especially in terms of drug management and storage. The findings also indicate the need for stricter law enforcement as well as increased training for pharmacists in understanding ethics and regulations. Conclusion: dispensing expired medicines has the potential to cause serious health impacts, including decreased drug efficacy and increased risk of side effects for patients. To address violations in the management of expired drugs, the relevant regulations provide for strict law enforcement as a sanction for violators, so as to encourage compliance with existing standards. In addition, legal protection for patients is stipulated in the law, which guarantees their right to obtain safe and quality medicines, in accordance with established quality standards. Keywords : Expired medication; pharmacy code of ethics; pharmaceutical work